2014
DOI: 10.1007/s11270-013-1831-7
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel Co-Product (BCP) Decreases Soil Nitrogen (N) Losses to Groundwater

Abstract: This study compares a traditional agricultural approach to minimise N pollution of groundwater (incorporation of crop residues) with applications of small amounts of biodiesel co-product (BCP) to arable soils. Loss of N from soil to the aqueous phase was shown to be greatly reduced in the laboratory, mainly by decreasing concentrations of dissolved nitrate-N. Increases in soil microbial biomass occurred within 4 days of BCP application—indicating rapid adaptation of the soil microbial community. Increases in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 70 publications
1
18
0
Order By: Relevance
“…In a recent study, glycerol was also found to significantly reduce N loss through minimizing nitrate leaching, owing to microbial immobilization of N [4]. Other bioenergy byproducts with highly available C have also found to cause a short-term immobilization of N [1].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In a recent study, glycerol was also found to significantly reduce N loss through minimizing nitrate leaching, owing to microbial immobilization of N [4]. Other bioenergy byproducts with highly available C have also found to cause a short-term immobilization of N [1].…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Qian et al [18] reported that N supply from urea fertilizer was adversely affected by glycerol application, especially at the high rates, leading to a significant reduction in plant growth and N uptake. Under growth chamber conditions, glycerol amendment was also shown to immobilize soil available N, as shown by small supply rates of NO 3´-N and NH 4 + -N measured in the soil [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BCP was selected as a C substrate to support microbial metabolism owing to a global and pressing need to reconcile issues of food security and bioenergy through integrated synergies (Redmile-Gordon et al., 2015b, Kline et al., 2016). The growing range of uses for BCP in soils ranges from the capacity to reduce direct N 2 O emissions (Alotaibi and Schoenau, 2013) preventing NO 3 − contamination of groundwater (Redmile-Gordon et al., 2014a) and supporting production of EPS via the native soil microbial biomass (Redmile-Gordon et al., 2015b). …”
Section: Introductionmentioning
confidence: 99%
“…More direct uses of BCP offer intriguing environmental prospects, e.g., as a component of soil treatments to engineer improved (or repair lost) soil functions. The application of BCP to soil as a substrate for the native soil microbial biomass was previously found to be > 99% effective in causing nitrate (NO 3 ) capture from soil solution and thus preventing loss from surface horizon (23 cm) in winter ( Redmile-Gordon et al, 2014a ). BCP therefore has considerable potential for improving nitrogen use-efficiency and limiting the environmental damage caused by ‘leaky’ agriculture.…”
Section: Introductionmentioning
confidence: 99%